2022
DOI: 10.3389/fnut.2022.918814
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Anti-cytomegalovirus Activity in Human Milk Following High-Pressure Processing Compared to Holder Pasteurization

Abstract: Pasteurized donor human milk is recommended for hospitalized preterm infants when mother’s own milk is unavailable. Our aim was to compare the antiviral activity of human milk processed by Holder pasteurization (HoP) or high-pressure processing (HPP) against representative enveloped and non-enveloped viruses including cytomegalovirus and hepatitis A virus. Expressed milk from 20 donors collected from the Ontario Milk Bank was combined into 10 pools, each from two unique donors. Each pool was processed by HoP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A few studies tested donated milk samples for CMV prior to pooling and pasteurization [ 24 , 25 ]. Bacterial and viral analysis of unpasteurized individual milk from an internet sharing source ( n = 101) compared to unpasteurized individual samples of milk donated to a milk bank ( n = 20) found that 21% of the internet samples were CMV DNA positive versus 5% of the human milk bank samples [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies tested donated milk samples for CMV prior to pooling and pasteurization [ 24 , 25 ]. Bacterial and viral analysis of unpasteurized individual milk from an internet sharing source ( n = 101) compared to unpasteurized individual samples of milk donated to a milk bank ( n = 20) found that 21% of the internet samples were CMV DNA positive versus 5% of the human milk bank samples [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pitino et al ( 48 ) reported the reduction of CMV (initial load of 10 5 PFU/mL) and hepatitis A virus (HAV) (initial load of 10 6 PFU/mL) below the detection limit (4 PFU/mL) for multiple HPP treatment tested (350–600 MPa; 8–10 min). Furthermore, Kothari and colleagues ( 47 ) reported a maintained anti-CMV activity in milk treated by one HPP-cycle of 500 MPa for 8 min. Therefore, HPP used in these conditions preserves antiviral activity.…”
Section: High Pressure Processing (Hpp)mentioning
confidence: 99%